Tilapia genetics and culture Proceedings of the seminar-workshop on tilapia genetics and culture Held at the Freshwater Aquaculture Center, Central Luzon State Univ.on 20-22 June 1985. (PCAMRD/ICLARM, 1989)
Book Series No.01; 1989